William Shakespeare : the tempest - Moseley, C. W. R. D. (Charles W. R. D.) (Literature insights., 2007)
Aims to introduce students with little or no prior experience of the field to the conclusions of recent scholarship and research into theatrical conditions, conventions and concepts in the time of Shakespeare.